Arachidonic acid treatment combined with low temperature conditioning mitigates chilling injury in cold‐stored banana fruit. (27th October 2021) - Wan, Chang; Tan, Piaopiao; Zeng, Chaozhen; Liu, Zhixiang
Summary: Cold‐stored banana fruit is particularly susceptible to chilling injury (CI). Over transportation and storage, CI is a key physiological factor affecting postharvest banana quality. Arachidonic acid (ARA) is considered a signal molecule that elicits stress signalling networks in plants. However, whether exogenous ARA treatment can reduce CI in postharvest fruit remains unknown. This study investigated the effects of a combination of exogenous ARA treatment and low temperature conditioning (LTC) on mitigating CI occurrence. ARA + LTC treatment decreased electrolyte leakage, accumulation of malondialdehyde, H2 O2 content, weight loss and occurrence of CI symptoms. This treatment also delayed fruit softening and colour development, and maintained both vitamin C and chlorophyll contents in bananas stored at 0 °C for 36 days. In addition, ARA + LTC treatment significantly increased the activities of ascorbate peroxidase, glutathione reductase, peroxidase, catalase and superoxide dismutase. Concluding, ARA + LTC treatment has the potential to reduce CI in banana fruit during cold storage. This makes it an effective postharvest technique for fruits and vegetables susceptible to CI. Abstract : Arachidonic acid treatment combined with low temperature conditioning mitigates chilling injury in bananas mainly by enhancing antioxidant capacity and maintaining membrane integrity.